2019
DOI: 10.3390/app9071463
|View full text |Cite
|
Sign up to set email alerts
|

Combined MvdXML and Semantic Technologies for Green Construction Code Checking

Abstract: The construction process plays a key role in sustainable development of the environment. With the concept of sustainable construction being put forward in the world, some countries released green construction standards to strengthen the requirements in the construction phase. Green construction code checking needs to integrate semantic information embedded in green construction standards and model information involved in Industry Foundation Classes (IFC) and/or Model View Definition (MVD), which are generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…In addition, it is possible to extend the IFC data structure in accordance with official standards according to buildingSMART [106]. Also, so-called model view definitions (MVD), as defined by buildingSMART could be used to create valid IFC sub-sets [107], which allow for BIM-LPS data exchange. All this was not possible at the time of the formulation of the original BIM-Lean interaction matrix.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is possible to extend the IFC data structure in accordance with official standards according to buildingSMART [106]. Also, so-called model view definitions (MVD), as defined by buildingSMART could be used to create valid IFC sub-sets [107], which allow for BIM-LPS data exchange. All this was not possible at the time of the formulation of the original BIM-Lean interaction matrix.…”
Section: Discussionmentioning
confidence: 99%
“…The proposal of the Industry Foundation Classes (IFC), which is a neutral file format to facilitate building related information interoperability in AEC industry, promoted some research for building rule compliance checking on this model schema [4]. IFC documents of building models were generally viewed as inputs in building model preparation phase [4,5]. Additionally, for some semantic ACC applications, IFC documents were generally converted into Resource Description Framework (RDF) standard model in the building model preparation phase [6,7].…”
Section: Automatedmentioning
confidence: 99%
“…A rule-based system was proposed to automate the code checking process for green construction. Still, the researchers found that the domain knowledge is dispersed and fragmented, and rule acquisition requires human experts from many professional fields [11]. Hu et al [7] applied the rules to identify the dependency relationship of conflicting/clashing components, thereby constructing a component-dependent network.…”
Section: Related Workmentioning
confidence: 99%
“…However, the constructing dependency relationships between components and query algorithms is often time-consuming and labor-intensive when acquiring and maintaining the rules. Jiang et al proposed a rule-based knowledge system to automate the code-checking process for green construction [11]. They found that the domain knowledge is usually dispersed and fragmented, so rule acquisition requires human experts from many professional fields.…”
Section: Introductionmentioning
confidence: 99%